Title to Submerged Lands Beneath Tidal and Navigable Waters : hearings before the United States Senate Committee on the Judiciary, Eightieth Congress, second session, on May 4, 5, 1948. (U.S. Congressional Hearings., 1948)
Considers legislation to confirm the title of states to lands and resources in and beneath navigable waters within state boundaries. Also considers dispute between the state of California and the Federal Government over the proper title to lands off the coast of California.